Differences by sex and age in motor coordination in schoolchildren from Cúcuta city - Danny Daniel Carrillo Benitez; Brian Johan Bustos-Viviescas; Carlos Enrique García Yerena; Amalia Villamizar Navarro; John Alexander García Galviz (Medisur)
Foundation: motor coordination has been and will be one of the most important components in the physical education area, since it allows synchronizing and coordinating the muscles movements and extremities of the body, in order to enable the performance of various activities. Objective: to determine the motor coordination level differentiated by age and sex in schoolchildren. Methods: research carried out at the Mariano Ospina Rodríguez Educational Institution, which included schoolchildren from six to eleven years of age, to whom the 3JS test was applied, which consists of seven tests battery to determine the motor coordination level in children. Results: there were very significant differences when comparing the children motor coordination regarding all the age ranges studied (6-7 years vs 8-9 years; 6-7 years vs 10-11 years; 8-9 years vs 10 -11 years) (p<0.01). The girls obtained very significant differences when comparing the groups of 6-7 years with respect to that of 8-9 years and 10-11 years (p<0.01); however, when comparing boys and girls by age range, only the 10-11 year old group presented significant differences in motor coordination (p<0.01). Conclusions: the results allow us to infer that it is important to evaluate and develop activities according to the child maturation stage to determine more specific jobs for girls, since in this work and in many studies carried out, a significant difference was identified in terms of their motor development.